Supply Chain Strategy for Convergence of Regional Economic Growth East Coast North Sumatera, Indonesia - T. Zulham; Sirojuzilam Sirojuzilam; Syaiful Bahri; Jumadil Saputra (International Journal of Supply Chain Management, 2019)
Convergence as the core theory of growth in 1990, based on the hypothesis put forward by Barro and Sala-i-Martin (1995) using the neoclassical growth model. One important aspect of this model has been studied and analyzed seriously as an empirical hypothesis of convergence with the assumption that the preferences and apply the same technology.The estimation results above show the value of (1 + Î²) of 0.7660. Based on these values, the value of Î² is known of -0.234. Î’ value (0.2340) is between zero and -1 indicates that there is a process of convergence of economic growth among the districts / cities in North Sumatra, East Coast Region at the speed of convergence of 23.40%. AndConditional convergence models have a higher speed than the absolute convergence models. This indicates that the independent variable (GRDP/capita, working population, number of poor and length of studyhas a great influence in increasing the speed of convergence of economic growth in the East Coast region of North Sumatra.